PENERAPAN VLAN DALAM MITIGASI SERANGAN DDOS PADA OLT HSGQ DAN ROUTER MIKROTIK - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Yuliadi Yuliadi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
DDoS is a threat that often disrupts server availability resulting in network devices becoming powerless. In Indonesia, it was recorded that the results of anomaly detection obtained the source IP address and destination IP address, with the country detected as a threat actor who has the potential to use the IP address as a proxy to disguise the real IP address of the threat actor being the first country in Indonesia with 124 million sources of anomalies. OLT and routers are important components in computer network infrastructure by managing data traffic between network devices and users. VLAN is a technology for separating a logical network from a physical network that can help secure the network against DDoS attacks. By using VLANs, it is possible to group different traffic to mitigate the impact of DDoS attacks and protect the network infrastructure. VLAN implementation in mitigating DDoS attacks on HSGQ OLTs and Mikrotik Routers faces technical challenges such as proper configuration, traffic monitoring, and security management. This research is expected to provide insight for network professionals and security researchers in order to improve the security of computer network infrastructure